Prevalence of Hepatitis B, C and HIV Viruses among Hemophiliac Patients in Al-Anbar Governorate - Hussein Ali AL-Enzy1 Fakhri Jamil Al-Dalla Ali2 , Adnan M Jasim3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: People with hemophilia (factor VIII and IX deficiency) and those with other clotting factordeficiencies are particularly at risk of acquiring blood-borne hepatitis virus infections and HIV throughtransfusion with unscreened blood and blood products.Objective: To estimate the prevalence of hepatitis B, C, and HIV among hemophiliac patients in the AlAnbar governorate.Patients and methods: A cross-sectional study carried out between October 2014 and March 2015 wasdone to estimate the prevalence of hepatitis B, C, and HIV among hemophiliac patients. Forty hemophiliacpatients were recruited to this study, who were documented to have hemophilia A and B by factor assay.Patients’ surveillance for hepatitis B, C and HIV were done by the electrochemiluminescence immunoassay“ECLIA” by using Cobas e 411-immunoassay analyzer.Results: Forty hemophiliac patients with age ranged between 6 months and 22 years with mean age 9.9 ±5.4 years were recruited to this study, 5 patients were mild hemophilia, 6 patients moderate hemophilia and29 patients with severe hemophilia.The prevalence of hepatitis C among the 40 hemophiliac patients was 5%, while for hepatitis B and HIV was0%. Six patients (15%) showed immunity to hepatitis B due to successful vaccination.Conclusions: This study showed that the prevalence of hepatitis B and HIV is zero, while for hepatitis C5%. Hepatitis C infection was more in severe hemophilia A, advanced age and an increasing number ofblood and blood products transfusion. Only 6 patients (15%) among hemophiliac patients were seropositivefor hepatitis B vaccine immunity.